A Case Report on Post-Transplant Erythrocytosis (BIRDEM Medical Journal, 2019)
Post-transplant erythrocytosis is defined as persistently elevated haemoglobin and haematocrit levels that occur following renal transplantation and persist for more than six months in the absence of thrombocytosis, leukocytosis or other potential causes of erythrocytosis. Here, we report the case history of a 35-year-old male, who underwent live related kidney transplantation ten months ago, presented with high haemoglobin level and high haematocrit. It is an uncommon complication of kidney transplant recipient,whichprompted us to report the caseBirdem Med J 2019; 9(2): 170-173